Hubungan Pola Komunikasi Klinik Pratama dengan Kualitas Pelayanan terhadap Pasien di Klinik Pratama - Fatmah Al-Hulaibi; Moc. Subur Drajat (UNISBA Press, 2024)
Abstract. Health issues and challenges in Indonesia are still a serious concern for the government. With the increasing standard of living in Indonesian society in general, awareness of the importance of health is still relatively low. In this case, health services should not only contain healing services but also include preventive services to improve the quality of life and provide satisfaction for consumers as recipients of health services. This is the background for researchers to conduct research on